Mental Health Status and Its Impact on TB Treatment and Its Outcomes: A Scoping Literature Review - Agbeko, Charles Kwaku; Mallah, Manthar Ali; He, Biyu; Liu, Qiao; Song, Huan; Wang, Jianming (Frontiers in Public Health, 2022)
Background Tuberculosis (TB) infection interferes with the health-related quality of life (HRQOL), including physical, social, mental, emotional and financial domains of individuals. The goal of this scoping review is to outline the most frequent mental issues encountered by TB patients and evaluate the effects of mental health on TB treatment outcomes. Our findings identify research gaps that could help bridge the overall treatment outcomes in the near future. Method A systematic stepwise approach was adopted to search online resource databases like PubMed, Web of science, and gray literature to retrieve published scientific articles for the review. Titles and abstracts of selected studies were examined for their possible eligibility. The studies matching our eligibility criteria were taken into account for this scoping review. Results One hundred and ninety three articles were retrieved out of which 26 met the final inclusion criteria. We found that studies adopting interventional approaches reported good mental wellbeing outcomes and better medical compliance as compared with studies that just investigated the subjects. The data represented 15 countries including three low-income countries (LICs), four low-middle-income-countries (LMICs), seven upper-middle-income countries (UMICs), and one high-income country (HIC). Conclusion Depression, anxiety, and poor social support, and stigma affect the wellbeing of individuals across the globe irrespective of age, race, demographic characteristics, geographical location, and social status.